ANALISIS SISTEM INFORMASI AKUNTANSI PERSEDIAAN PADA PT. MUKTICITRA PERKASA - Devy Yulvia Ratna Sary, Clara; Rosalia Purbaya, Serafi (Universitas Pawyatan Daha, 2022)
The role of the inventory accounting information system implemented by the company is expected to provide benefits to company leaders and managers, especially in decision making and in determining the steps to be taken by the company, especially in carrying out production process activities to run smoothly. Therefore, the inventory accounting information system is expected to be a supporting element for a company in supporting the smooth production process.The results of this study indicate that the recording of the accounting cycle should be carried out in accordance with the accounting system, where the data will start from the transaction to the time of reporting. The recording that occurs will be more planned and can find out the deviations that occur so that management can more easily make correction and improvement efforts earlier. Therefore, it is necessary to have better inventory management that can inform funding problems in the company.